2018
DOI: 10.1038/s41556-018-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-cell-secreted exosomal miR-105 promotes tumour growth through the MYC-dependent metabolic reprogramming of stromal cells

Abstract: Cancer and other cells residing in the same niche engage various modes of interactions to synchronize and to buffer the negative effects of environmental changes. Extracellular miRNAs have been recently implicated in the intercellular crosstalk. Here we show a mechanistic model involving breast-cancer-secreted, extracellular-vesicle-encapsulated miR-105, which is induced by the oncoprotein MYC in cancer cells and in turn activates MYC signaling in cancer-associated fibroblasts (CAFs) to induce a metabolic prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
299
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(306 citation statements)
references
References 64 publications
4
299
1
2
Order By: Relevance
“…This suggests that tumor‐derived Exos metabolically alter the activated fibroblasts and potentially contribute toward metabolite sharing between tumor and CAFs that is critical for tumor progression . The role of cancer Exos in metabolic reprogramming of stromal fibroblasts is only beginning to emerge . Breast cancer Exos have been shown to reprogram glucose metabolism in pre‐metastatic cells to promote metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that tumor‐derived Exos metabolically alter the activated fibroblasts and potentially contribute toward metabolite sharing between tumor and CAFs that is critical for tumor progression . The role of cancer Exos in metabolic reprogramming of stromal fibroblasts is only beginning to emerge . Breast cancer Exos have been shown to reprogram glucose metabolism in pre‐metastatic cells to promote metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…In ourprevious study, we performed a Kyoto Encyclopedia of Genes and Genomes pathway analysis of overlapping proteins in TMVs and found that proteins involved in metabolic pathways were the most abundant (11). Although the roles of cancer microenvironment–derived MVs in modulating cancer cell metabolism have been reported, the role of TMVs in stromal metabolic reprogramming was less studied (2427). Thus, we examined the role of TMVs in modulating stromal metabolic alteration in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…We further verified that ZNF205‐AS1 increased EGR4 mRNA stability, and therefore up‐regulated EGR4 expression. microRNAs (miRNAs) are well‐known to bind the 3’UTR of target mRNAs and induce the degradation and/or translation inhibition of target mRNAs . The interaction between ZNF205‐AS1 transcript and EGR4 mRNA 3’UTR may protect EGR4 mRNA from miRNAs‐induced degradation, which need further investigation.…”
Section: Discussionmentioning
confidence: 99%